Overview of home nutritional care for children and adolescents followed by the Better at Home Program - Correia Simões, Fernanda (2025)
In Brazil, the Home Care Service of the Unified Health System, through the Better at Home Program, has been expanding its activities to care for children and adolescents, a population whose nutritional care is essential. The objective of this article was to describe the panorama of home nutritional care for children and adolescents followed by the Better at Home Program, in different Brazilian regions. This is a cross-sectional study with nutritionists from the Better at Home Program, who answered an electronic form with questions regarding the professional’s profile, the pediatric population served and the conditions offered for nutritional monitoring. Seventy questionnaires were analyzed from all regions of the country, with an average of 7.6 pediatric patients being monitored by each nutritionist, presenting chronic health conditions, dependence on technology and enteral feeding of the home-based and/or industrialized type, with significant regional differences regarding this profile. More than 70% of professionals responded that the city has an enteral diet supply program, but not all equipment for nutritional assessment is offered in the same way in Brazil. Home care nutritionists still face challenges and the systematization of pediatric care at home would facilitate nutritional care for this population.